PENGARUH TINGKAT PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT KARYA SAWITINDO MAS (KSM) - Subandrio Subandrio; Asminawati Asminawati ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
This research was conducted at PT KSM (Karya Sawitindo Mas) Tanjung Alai Village, Lubuk Pinang District, Mukomuko Regency, Bengkulu Province. This research is a quantitative research in which the researcher proves by using numbers on a number of populations and samples that are considered worthy of research. This method is used to examine statistical data in order to be able to test a hypothesis obtained by the research field. Based on the results of hypothesis testing using the t test, the Education Level variable has a positive and significant effect on employee performance, this can be seen from the results of the t test which states the t value of sig < = 0.000 < 0.05). The results of t-test of work experience variable also show a positive and significant influence result on employee performance, this can be seen in the value of t-test result which states that t sig <Î± = 0.000 < 0.05). The results of the analysis above show that the level of education and work experience has an influence on employee performance, this can be seen in the f test which shows the value of t sig <Î± = 0.000 < 0.050), so it can be concluded that H_3 is accepted, meaning that simultaneously the variable of education level and work experience has an influence on employee performance at PT KSM (Karya Sawit Indomas) employees.â€ƒÂ Keywords: Education Level, Work Experience and Employee Performance.